Ang maging babae sa pulang larangan [to become a woman in the red front] : a research-based screenwriting chronicling women in the Philippine contemporary revolutionary movement - Caralde, Mae Go Urtal 1975- (College of Mass Communication, University of the Philippines Diliman, 2013)
"This thesis probed and gathered narratives of contemporary women revolutionaries and attempted to appropriate a process in screenwriting wherein the revolutionary woman is redifined, reconfigured and represented as a central motif in the story. It is the contention of this study that while women revolutionaries are somehow represented or portrayed in films, there are more marginalized and unheard voices that need to surface, and that may shed light to important discourses on women, her role in the revolution and her role in society. By using Foucault's theory on discourse, this study delved into the particularities of revolutionary life and of how one molds herself to be a revolutionary woman by looking not on the continuities or unifying elements of the respondent's narratives and of their revolutionary ideals, but more so on identifying the gaps, nuances and the surrounding elements that brong about our knowledge of women and their roles in the revolution. The second phase of this study demonstrates how revolutionary women could be appropriately represented in their plurality through a screenplay with multiple characters. The screenplay is constructed along the concept of social realism. That even if women are the main notif of the story, it alternately foregrounds society as the character in itself interposing the need for social mobilization if women issue must be addressed."